Pembinaan Keluarga Prasejahtera dalam Meningkatkan Pemberdayaan Ekonomi Melalui Program Rumah Pangan di Dompet Sosial Madani Wilayah Jembrana Bali - Rafika, Diah; Kusjuniati, Kusjuniati; Kurniawati, Kurniawati (Maisyatuna, 2020)
DSM's efforts in helping the government to reduce poverty. One of the things done by DSM is to create a Food House as a form of program for underprivileged families in Bali. The purpose of this study was to determine: 1) Fostering underprivileged families through a food house program in the DSM Jembrana region of Bali. 2) Efforts for economic empowerment for underprivileged families through a food house program in the DSM Jembrana region of Bali. and 3) The results of fostering underprivileged families through a food house program on the family economy in the DSM Jembrana region of Bali. This type of research is descriptive with a qualitative approach. Descriptive qualitative research and using purposive sampling technique. The author uses three techniques namely; interviews, observations and documentation. Data analysis techniques include; data reduction, data presentation and decision making. Based on the results of this study indicate that the underprivileged families and DSM parties who have been studied and interviewed regarding the development of underprivileged families have the stages of the process to be able to follow the guidance of the food house program, after being investigated the economic empowerment efforts that DSM has done have received a good response by members because it is very helpful increase income with the facilities provided and the results obtained after coaching is done is a change in the behavior of members and members can meet their daily needs.